Manajemen Majlis Ta’lim dalam Meningkatkan Pemahaman ‘Ubudiyah dan Mu’amalah - Mohammad Fahrur Rozi; Suhaimi; Jamiliya Susantin (Kariman: Jurnal Pendidikan Keislaman, 2023)
The management of taklim assembly is very important in increasing people's understanding of mu'malah and 'ubudiyah because people in everyday life cannot be separated from their daily needs. Therefore, changes in planning, leadership, material for the taklim assembly need to be changed or renovated in order to increase the understanding of the taklim congregation. The understanding of the majlis taklim congregation can increase faith and piety not only in the spiritual aspect but also in the cognitive and psychomotor aspects, so that the majlis taklim congregation can further strengthen their faith and piety with religious practices and religious tourism.